ISLAM DI KESULTANAN BANJAR PADA ABAD KE 19 M DAN PERAN MUHAMMAD ARSYAD AL-BANJARI - Abd. Gafur (Lembaga penelitian dan pengabdian kepada masyrakat, 2009)
The islamization process community in the Sultanate of banjar society, has a very strong relationship with the Sultanate of Demak, after the collapse of the Majapahit kingdom (Hindus) has had a big hand in the first islamization prince sultan ocean. 16th century Muslim communities M still a minority, limited embraced by ethnic Malays, while ethnic Dayak untouched. The spread of Islam has been running a vigorous and intensive when launched by Muhammad Arsyad al Banjari (1122-1227 H / 1710-1812 AD). With persistence, tenacity, and science has, Islam really flourished in his time in the empire Banjar